2021
DOI: 10.3390/cancers13153756
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Localization of RXRα Determines Outcome in Breast Cancer

Abstract: The aim of this retrospective study was to assess the prognostic value of cytoplasmic versus nuclear RXRα expression in breast cancer (BC) tissue samples and to correlate the results with clinicopathological parameters. In 319 BC patients, the expression of RXRα was evaluated via immunohistochemistry. Prognosis-determining aspects were calculated through uni- and multivariate analyses. Correlation analysis revealed a trend association with nuclear RXRα expression regarding an improved overall survival (OS) (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
2
7
0
1
Order By: Relevance
“…Within this study, we combined the analysis of TIL levels (following Salgado’s guidelines), peritumoral inflammation (adapted from Klintrup criteria), and nuclear receptor expression in a cohort of BC in relation to patient overall survival (OS). Taking into account both nuclear and cytoplasmic expression of type I and II nuclear receptors, as former studies already showed a prognostic impact of nuclear receptor subcellular localization [ 40 ], our results highlight a strong interplay of the two parameters, which determines their prognosis value for BC patients. Next to the influence of TILs on tumor progression and prognosis, the nuclear receptors and their subcellular localization play notable roles in the pathophysiology of BC as well [ 34 , 42 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Within this study, we combined the analysis of TIL levels (following Salgado’s guidelines), peritumoral inflammation (adapted from Klintrup criteria), and nuclear receptor expression in a cohort of BC in relation to patient overall survival (OS). Taking into account both nuclear and cytoplasmic expression of type I and II nuclear receptors, as former studies already showed a prognostic impact of nuclear receptor subcellular localization [ 40 ], our results highlight a strong interplay of the two parameters, which determines their prognosis value for BC patients. Next to the influence of TILs on tumor progression and prognosis, the nuclear receptors and their subcellular localization play notable roles in the pathophysiology of BC as well [ 34 , 42 ].…”
Section: Discussionsupporting
confidence: 62%
“…Using the above-described BC cohort, the expression of type I and type II nuclear receptors has been previously analyzed by immunohistochemistry by our group. Information was specifically evaluated regarding ERα and PR [ 34 ], PPARγ [ 35 ], thyroid hormone receptors (TRs) [ 36 , 37 ], AhR [ 33 ], LXR [ 38 ], and RXRα [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Of note, various types of addiction to specific transcriptional programs and/or kinase activities appear to operate in specific subsets of cancer and are thought to deeply contribute to cancer pathogenesis [77,78]. Interestingly, when a more accurate and stringent analysis was performed on the regulated target genes of these two candidate miRNAs, Mienturnet analysis followed by MetaCore process networks revealed the presence of important central hubs, including the transcriptional factors SP1 (specificity protein 1), RXRA (retinoid X receptor alpha), and BMI-1 (polycomb ring finger proto-oncogene) and the epidermal growth factor receptor kinase EGFR, with multiple roles in breast cancer development and progression [79][80][81][82]. Moreover, Metacore gene enrichment analysis indicated the involvement of the 18 target genes in cell cycle transition from G2 to M, the follicle-stimulating hormone (FSH) beta signaling pathway, androgen receptor signaling cross-talk, NOTCH signaling, ESR1 nuclear pathway and signaling, and EMT among the top enriched processes.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the well-known nuclear receptors, others, including the retinoid X receptor (RXR), thyroid hormone receptors and vitamin D receptor, play a significant role in the pathophysiology of breast cancer. The study by Zheni et al aimed to assess the prognostic value of nuclear versus cytoplasmic retinoid X receptor α (RXRα) expression by immunohistochemistry in 319 breast cancer patients [ 11 ]. In their findings, the expression of cytoplasmic RXRα is correlated with a more aggressive disease, whereas nuclear RXRα expression appears to be a protective factor.…”
mentioning
confidence: 99%